Effects of supplementation of rumen protected fats on rumen ecology and digestibility of nutrients in sheep - Behan, Atique Ahmed; Loh, Teck Chwen; Fakurazi, Sharida; Kaka, Ubedullah; Kaka, Asmatullah; Samsudin, Anjas Asmara @ Ab Hadi (MDPI, 2019)
Rumen protected fats (RPF) are known to improve animal performance without affecting rumen metabolism in sheep. However, comparative effects of prilled fat, prilled fat with lecithin and calcium soap have not been fully studied. Hence this experiment was planned using 36 male Dorper sheep in a completely randomized design in four treatment groups. The diets included: Basal diet (70:30 concentrate to rice straw) with no added RPF as a control (CON), basal diet plus prilled fat (PF), basal diet plus prilled fat with lecithin (PFL) and basal diet plus calcium soap (CaS). The trial lasted 90 days following two weeks adaptation period. The body weights, average daily gain and gain to feed ratio were not affected by treatments. The intake and digestibilities of dry matter, organic matter, crude protein and neutral detergent fibre were not affected, while those for ether extract and crude fibre differed (p < 0.05). RPF had no effect on concentrations of ammonia nitrogen, total volatile fatty acids and total bacterial population. The concentrations of rumen total saturated fatty acids, unsaturated fatty acids, total n − 3, total n − 6, unsaturated fatty acids:saturated fatty acids and polyunsaturated fatty acids:saturated fatty acids differed (p < 0.05) among the treatments with RPF supplementation. Hence supplementation of different types of protected fats did not influence animal performance in Dorper sheep.